Ceramica fine da mensa in età tardoantica a Bergamo. Consumi, commerci e produzioni locali - Gorla, Davide (Rei Cretariae Romanae Fautorum Acta, 2023)
Bergomvm was a small Roman city located on the hills at the foot of the Alps in Northern Italy and far away from the main trade routes that crossed the Po Valley. This text analyzes the consumption of terra sigillata (both locally produced and imported) and the trade relations of the city in Late Antiquity. Local terra sigillata is the most abundant, especially from the second half of the 2nd to the 4th century AD and is inspired by the contemporary forms of ARS and Gaulish sigillata. ARS is mainly represented by the fabric D. It appears in the 4th century AD and it is still attested in the 6th and 7th century AD. Gaulish sigillata is very rare and is only certainly attested with a cup produced in Rheinzabern. The tablewares are mainly concentrated in two places: almost all the fragments of ARS come from the area of the forum; the most refined pieces and later ones (6th-7th AD) come from the domus of Vicolo Aquila Nera. The Mediterranean goods arrived from the Adriatic ports to Bergamo through the Po and Oglio rivers. The last stretch over land was by the Bergomvm-Brixia road.